160k views
0 votes
How to solve this in steps?

How to solve this in steps?-example-1
User Zxcat
by
5.9k points

2 Answers

5 votes

4a + 5 = 3(a - 7) + 2a

Start by distributing the 3 on the right side.

4a + 5 = 3 * a - 3 * 7 + 2a

4a + 5 = 3a - 21 + 2a

Now combine like terms on the right side. The like terms are 3a and 2a. They add up to 5a.

4a + 5 = 5a - 21

Subtract 5 from both sides.

4a = 5a - 26

Now subtract 5a from both sides.

-a = -26

Divide both sides by -1.

a = 26

User Shay Rybak
by
5.1k points
2 votes

4a + 5 = 3(a - 7) + 2a
4a + 5 = 3a - 21 + 2a
4a + 5 = 5a -21
4a -5a = -21 -5
-a = -26
a = 26

User VIBrunazo
by
5.7k points